MENGGAGAS TUHAN BERDIMENSI BARU (Sebuah Risalah Tauhid) - Ngimadudin Ngimadudin (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2018)
The struggle for the search for the intrinsic values of identity and the dimension of humanity is always in turmoil. The efficacy of the age coupled with the advancement of digital technology requires that humans also renew the perspective of essential values and spiritual dimensions in response to values outside the transcendental corridor. Spiritual position (metaphysical) as the most unique thing in human beings must be able to understand also things outside the physical body of the human being which are also transcendental. In the age of modern technology, transcendental discourse experienced a sharp degradation of specialization in the depth of the person. Because humans are not interested in things that are not rational. The progress of the age is rationality, therefore expressing the dimension of godliness must place oneself on new essential values that can be captured by the human mind in a real way.